The Theory of Accumulation A Marxian Approach to the Dynamics of Capitalist Economy - Okishio, Nobuo (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book treats the mechanisms of growth and cycles in capitalist economies in a unified manner, incorporating a highly original macro-dynamic theory based on Marxian micro-foundations and historical perspectives. That theory was developed about 50 years ago by Nobuo Okishio (1927-2003) and included the ideas of Keynes and Harrod. In mainstream economics, it used to be standard to analyse long-term economic growth and business cycles in different frameworks. That approach has been changing recently, but it still tends to be common to discuss them separately. At the outbreak of the global financial crisis of 2007-2008 and the prolonged stagnation that followed, there was strong criticism among policymakers and businesspeople that mainstream macroeconomics failed to provide convincing explanations and effective policy recommendations. This book offers an alternative perspective that responds to those criticisms. All these macroeconomic difficulties call for new wisdom beyond the limited neoclassical framework. The sharp, wise thoughts of Okishio will add new tools for young researchers worldwide to meet the challenges of the current resource misallocation, the Great Recession and the Lost Decades problems. Okishio proposes a historical perspective for the capitalist system, first. He argues that production relations are conditioned by productive force. The former should evolve as the latter improves, and the latter should evolve in order for human society to survive. While reproduction is indispensable for the economy to continue in any production relations, it takes a specific form in capitalist economy. He next shows that the existence of profit requires the exploitation of the labourer. This is called the Fundamental Marxian Theorem. He also shows a trade-off relationship between the real wage rate and the profit rate. In his theory, the real wage rate is determined to clear commodity markets in the short run as in the Keynesian theory, while Marx believed that the real wage rate is given at subsistence level or is influenced by the labour market. Okishio attributes the origin of the business cycle to labourers' under-consumption and private capitalists' dispersive decision of accumulation. The former is caused by exploitation, and the latter is based on the capitalist class's private ownership of the means of production. Both are derived from the nature of the capitalist economy. He argues lastly that, in the long term, the development of productive force through the business cycle will transform the production relation into a new economic system.
Preface -- 1.Introduction -- 2.Fundamental Structure of Capitalist Economy -- 3.Extended Reproduction in the Capitalist -- 4.Accumulation and Crisis in Capitalist System Economy -- 5.Tendency Law in Capitalistic Accumulation -- 6.A Vision Toward New Society.
Keywords: Economics-History.; Macroeconomics; Economic development; Marxian economics; Economics; History of Economic Thought and Methodology; Macroeconomics and Monetary Economics; Economic Growth; Marxist Economics; Political Economy and Economic Systems